ANALISIS KINERJA KEUANGAN PT.HM.SAMPOERNA DENGAN PT.WISMILAK Tbk PERIODE 2020-2021 - Franky Putra; Sri Hermuningsih (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to analize a comparison of financial performance at PT. HM SAMPOERNA Tbk. with PT. WISMILAK in 2020 and 2021. The research method used in this research is quantitative with manual calculations. The results of the study prove that there are several financial performances that show differences between PT HM SAMPOERNA Tbk. with PT. WISMILAK Tbk.